The Idea of Rasa in the Indian Theatre (Itinera, 2017)
This communication presents the notion of rasa in the Natyasastra, founding book of the theory of the theatre in India. This term defines the emotional state of the viewer needs the theater. The first meaning of the word rasa is sap, or juice of plants. One speaks, for example, of the rasa of the sugar cane that is what conveys the flavor of the cane sugar. The aesthetic experience is therefore presented as a tasting. Rasa is sensuality, proximity, experience. It is aromatic, it fills the space, absorbed by the body, it becomes a part, it works from the inside. Its means are similar to those in the kitchen : the combination and transformation of distinct elements in a new offering of the flavours mix. The Indian theatre prefer experience in distancing, the action of taste to that of judge. Author, actor, spectator, all have links, although different, with him rasa.